Siglec-E augments adipose tissue inflammation by modulating TRAF3 signaling and monocytic myeloid-derived suppressor cells during obesity - Rakib, Ahmed; Mandal, Mousumi; Al Mamun, Md Abdullah; Kiran, Sonia; Yasmen, Nelufar; Li, Lexiao; Collier, Daniel M.; Jiang, Jianxiong; Park, Frank; Singh, Udai P. (Frontiers in Immunology, 2025)
BackgroundObesity is associated with dysregulated metabolism and low-grade chronic inflammation in adipose tissue (AT). Immune cells, including macrophages, T cells, and neutrophils, infiltrate the AT and secrete proinflammatory cytokines to exacerbate the AT inflammation. RNA-Seq analysis of AT immune cells isolated from mice fed a high-fat diet (HFD) versus normal fat diet (ND) identified a panel of genes that were markedly downregulated, including sialic acid-binding Ig-like lectin E (siglec-E), in HFD compared to ND mice.MethodsA series of experiments in wild-type (WT) and siglec-E knockout (siglec-E KO) mice was designed to investigate the effect of HFD on the functional role of siglec-E in the regulation of AT inflammation and adipogenesis. We analyzed the changes in immune phenotypes, inflammatory response, adipogenesis, and levels of cytokines and chemokines after HFD and ND feeding.ResultsHFD consumption significantly increased the body weight and blood glucose levels in siglec-E KO mice relative to those of WT mice. This was associated with an increased infiltration of macrophages, CXCR3 expressing CD8 T cells, and monocytic myeloid-derived suppressor cells (M-MDSCs) with a concomitant decrease in numbers of dendritic cells (DCs), in the AT of siglec-E KO fed HFD versus the WT HFD counterparts. The HFD-fed siglec-E KO mice also exhibited elevated expression of intracellular Akt and TNF receptor-associated factor 3 (TRAF3) signaling, inducing C/EBPα, FASN, PPARγ, and resistin in suprascapular AT compared to WT HFD-fed mice. Taken together, these results suggest that a genetic deficiency of siglec-E plays a key role in inducing AT inflammation by differentially altering M-MDSCs and CD8+CXCR3+ T cell function and adipogenesis by TRAF3 and Akt signaling in AT.ConclusionOur findings strongly suggest that modulation of siglec-E pathways might have a protective effect at least in part against AT inflammation and metabolic disorders.